Measuring change in farmers' self-efficacy within the context of managing perennial summer forage crops : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Agriculture and Environment at Massey University, Manawatū Campus, New Zealand - Drysdale, Douglas (Massey University, 2021)
There is a continual need to consider ways of improving agricultural extension as concern is expressed with the slow farmer uptake of complex new agricultural technologies. Existing agricultural extension research suggests psychological drivers, such as farmers’ self-efficacy beliefs, may be a key variable influencing farmers’ adoption of new technologies. The focus of this study was to firstly measure change in farmers’ self-efficacy as they participated in an innovative agricultural extension programme designed to support learning about the management of perennial summer forage crops (PSF). The second aim was to identify factors that may have enhanced or undermined changes in the farmers’ efficacy beliefs in this domain. Finally, this study aimed to explore how changes in farmers’ self-efficacy might influence their future practice. The participants in this study were thirty-five sheep and beef farmers from the Hawkes Bay, Manawatū and Wairarapa regions of New Zealand. The Riverside Farmer Learning Project (RFLP) provided the platform on which to measure change in farmers’ self-efficacy. A multiphase mixed methods research approach was adopted for this study. A Farmer Self-Efficacy Measurement survey (FSEM) was developed to measure change in farmers’ self-efficacy within the domain of managing PSF. Semi-structured interviews, focus group discussions and field observations provided the opportunity to identify factors that enhanced or undermined changes in farmers’ self-efficacy to manage these forage crops. This study found that farmers’ self-efficacy increased during their 18-month involvement in the RFLP. The project’s collaborative style of knowledge sharing, as well as the opportunity to observe and share experiences with valued peers served to enhance the farmers’ self-efficacy and facilitated new learning about managing PSF. A lack of easily sourced, scientifically robust information concerning the economic effect of PSF weed and plant health management served to undermine the farmers’ self-efficacy within this domain. These new understandings and increased self-efficacy beliefs supported improved practices that lead to the potential to increase farm production. The results of the study suggest that a farmer’s belief in their ability to initiate change in the future is reliant on past successes that employed practices based on scientific evidence. The study also suggests that vicarious experiences are important for farmers where they can observe and talk about the practices of other farmers who have successfully made changes within their farm system, and engage in dialogue with scientists whose research interests focus on the domain of farmer learning. Considering how farmers’ new understandings and self-efficacy beliefs may shape future changes in farm practices, this study provides evidence regarding future development in the design of agricultural extension programmes.
Keywords: Forage plants; Farmers; New Zealand; Psychology; Self-efficacy; Evaluation; Agricultural extension work; 300202 Agricultural land management